ESTIMATION OF EFFECTIVENESSOF RADIOHYDROGEOLOGICAL MONITORING IN THE INFLUENCE ZONE OF KYIV RADIOACTIVE WASTE STORAGE - Scherbak, O.; Koshliakova, T.; Dolin, V.; Rudenko, I.; Kutska, Ya. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The current state of radiohydrogeological monitoring system in the influence zone of Kyiv subsurface radioactive waste storage is considered with using hydrogeological, statistical and geoinformatical research methods. According to monitoring observations (1992-2013) the spatialtemporal dynamics of the upper Quaternary – upper Eocene groundwater complex hydrodynamic regime is analyzed. Hydrogeofiltrational efficiency of the observation wells is estimated by two parameters, namely: the efficiency of uncovering of groundwater aquifer by filter section (filter position regarding the groundwater level and the rocks lithology in filter zone) and the transmissivity value. The presence of groundwater level downtrend and hydroizohypses spatial configuration changes were determined. The majority of observation wells are hydrogeofiltrational incomplete due to artificial mechanical mudding of the filter zone and structural features. Observational data provide little information and do not reflect the real impact of the storage on environment. Based on the results obtained the conclusion was made about the necessity of renewal and expansion of the current monitoring system. The monitoring system development must be made with taking into account the evolution of groundwater tritium contamination contours.